2014
DOI: 10.1007/s40618-014-0216-0
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of Nesfatin-1 levels in patients with OSAS associated with metabolic syndrome

Abstract: Nesfatin-1 which is known to play a role in the pathophysiology of insulin resistance can be a beneficial target in developing new therapeutic targets for treatment of patients with obesity without any toxic effects in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 22 publications
1
9
1
Order By: Relevance
“…In the present study, serum nesfatin-1 levels were lower in individuals diagnosed with metabolic syndrome. This result is similar to other studies investigating the metabolic syndrome and its components 21–24 26 27. In the present study, no significant difference was found between the BMI and body fat percentage of the case and control groups.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, serum nesfatin-1 levels were lower in individuals diagnosed with metabolic syndrome. This result is similar to other studies investigating the metabolic syndrome and its components 21–24 26 27. In the present study, no significant difference was found between the BMI and body fat percentage of the case and control groups.…”
Section: Discussionsupporting
confidence: 92%
“…It has been shown to stimulate glycose-dependent insulin secretion [28]. Low N1 levels have been reported to be responsible for IR and metabolic syndrome [29]. However, in the organism, the majority of hormones are in equilibrium.…”
Section: Discussionmentioning
confidence: 99%
“…Besides these few functional studies, in human sleep apnea syndrome an inverse correlation between NUCB2/ nesfatin-1 in peripheral circulation and the severity of disease was observed (Aksu et al 2015, Araz et al 2015, Shen et al 2015, whether there is a functional link remains to be elucidated.…”
Section: Sleepmentioning
confidence: 99%